Implementation of Cooperative Learning Model STAD (Student Teams Achievement Division) Type to Improve Student Motivation and Learning Outcames in Stoichiometry Material - Tarigan, Pasion; Herlinawati, Herlinawati; Panjaitan, Angel Shilvya; Rahmawaty, El Kamty Yamareta; Marbun, Intan Monika; Sitorus, Westy Natasya; Simanjuntak, Suryani (Universitas Lampung, 2024)
Stoichiometry is often considered challenging by students, as reflected in their low learning outcomes. This study aims to examine the impact of the Cooperative Learning model, specifically the STAD type, on students' motivation and learning outcomes in stoichiometry. The research utilized a quantitative method with a one group pretest-posttest design. Research instruments included a learning outcomes test and a motivation questionnaire. The findings revealed that this learning model significantly enhanced students' motivation and learning outcomes compared to conventional methods. Students in the experimental class demonstrated active participation in group activities and higher motivation, resulting in better academic performance. In conclusion, the implementation of the Cooperative Learning STAD type model effectively improves students' motivation and learning outcomes in stoichiometry.Keywords: Cooperative Learning, Implementation, Learning Motivation, Learning Outcames, StoichiometryDOI: 10.23960/jppk.v13.i3.32399